Curriculum Development: Enhancing Education Quality and Student Character in the Era of Globalization - Setiawan, Ruthnawaty; Rattu, Aubrey B.G.; Risakotta, Margreth Luciyanna (Indonesian Journal of Religious, 2023)
This article explores the development, implementation, and adaptation of the 2013 curriculum in Indonesia, with a particular focus on the challenges and opportunities faced by teachers in its execution. The study emphasizes the importance of understanding curriculum changes in the context of educational reforms, particularly in terms of integrating active learning and interdisciplinary approaches. The research highlights the role of teachers in adapting the curriculum to meet the diverse needs of students while maintaining the integrity and objectives of the national education system. Various perspectives on curriculum adaptation are examined, drawing from local and international studies, offering insights into the practical implementation challenges. The study concludes by providing recommendations for further research and improvements in the curriculum development process to enhance the effectiveness of education in Indonesia.